Preliminary osteogenic and antibacterial investigations of wood derived antibiotic-loaded bone substitute for the treatment of infected bone defects - Salamanna, Francesca; De Luca, Angela; Vandenbulcke, Filippo; Di Matteo, Berardo; Kon, Elizaveta; Grassi, Alberto; Ballardini, Alberto; Morozzi, Giacomo; Raimondi, Lavinia; Bellavia, Daniele; Costa, Viviana; Zaffagnini, Stefano; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
The development of reliable treatments for infected or potentially infected bone loss resulting from open fractures and non-unions is extremely urgent, especially to reduce the prolonged courses of antimicrobial therapy to which affected patients are subjected. Numerous bone substitutes have been used over the years, however today there are no effective solutions to treat critical bone loss, especially in the presence of infections. In the present study, the use of biomorphic calcium phosphate bone scaffold b.Bone TM , based on a next-generation resorbable biomimetic biomaterial, in bone reconstruction surgery of infection cases was evaluated. Using an 'in vitro 3D bone fracture model' to predict the behavior of this drug delivery system during critical bone loss in an infected (orWe have changed the title as suggested by reviewer1. potentially infected) site, the effects of scaffolds loaded with gentamicin or vancomycin on the viability and differentiation capacity of human mesenchymal stem cells (hMSCs) were evaluated. This scaffold when loaded with gentamicin or vancomycin exhibits a typical drug release curve determining inhibitory effects on the growth of Staphylococcus aureus, Enterococcus faecalis, and Escherichia coli, as well as relative biofilm formation. * 𝑑 𝛽𝑇𝐶𝑃We have modified the sentence to clarify the production step to reviewer 1. We also introduced the new reference and a flow chart diagram as a new image, as required.